2009
DOI: 10.1016/j.scitotenv.2009.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in coagulase negative staphylococci isolated from wastewater and drinking water

Abstract: This study reports the antibiotic resistance patterns of coagulase negative staphylococci (CNS) isolated from a drinking water treatment plant (WTP), a drinking water distribution network, responsible for supplying water to the consumers (WDN), and a wastewater treatment plant (WWTP), responsible for receiving and treating domestic residual effluents. Genotyping and the 16S rRNA gene sequence analysis demonstrated a higher diversity of species both in the WTP (6 species/19 isolates) and WWTP (12 species/47 iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 30 publications
7
71
2
Order By: Relevance
“…Under other circumstances, some species of coagulase-negative staphylococci can present a medical risk. Some coagulase-negative staphylococci (CNS) may behave as opportunistic pathogens, often introduced by medical devices or colonising exposed wounds (Veras et al 2008;Faria et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under other circumstances, some species of coagulase-negative staphylococci can present a medical risk. Some coagulase-negative staphylococci (CNS) may behave as opportunistic pathogens, often introduced by medical devices or colonising exposed wounds (Veras et al 2008;Faria et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary characterisation included Gram staining and tests for cytochrome c oxidase, catalase, and coagulase (Faria et al 2009). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of staphylococci has mainly been reported in polluted surface water [40] or in the biofilm from hospital wastewater [41]. In this study, eight out of ten species of coagulase-negative staphylococci identified (except for S. caprae and S. chromogenes) were also isolated from samples of drinking water and wastewater in Portugal [42]. The authors of the Portuguese study report dominance of S. pasteuri and S. epidermidis in samples taken from a drinking water treatment plant as well as from a drinking water distribution network.…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, none of the 57 CoNS isolates tested in the present study were resistant to gentamicin. Another study which isolated CoNS from Portuguese water supplies [42] found that antibiotic-resistant CoNS may colonize different types of water, including drinking water that fulfills all the quality standards. In agreement with our results, the Portuguese study also found CoNS species were resistant to β-lactams, tetracycline, clindamycin and erythromycin, the last of which was highly prevalent (34.7%).…”
Section: Discussionmentioning
confidence: 99%